STUDI ATAS PANDANGAN KAUM AGAMAWAN, PRAKTISI KESEHATAN DAN RESPONS MUI TERHADAP MASALAH ABORSI - Mustafid, Fuad (Al-Mazaahib: Jurnal Perbandingan Hukum, 2015)
Abortion is a classic problem that still continue to be discussed among experts and the public. It is perhaps because of the practice of abortion continues to occur from time to time with vary shapes and motifs. In Indonesia, talks and discussions on abortion also gone on long enough. The experts, both clerical and medical experts, involved in a heated debate on the issue of abortion. Nevertheless, the debate nevertheless did not come to fruition. On the other hand, the practices of abortion continues to occur in the wider community. The Council of Indonesian Ulama (MUI) felt obliged to give guidance to the Muslims in viewing and addressing the issue of abortion. In this case, the steps taken by the MUI issued a fatwa is the law. The MUI fatwa states that abortion is against their religion, so it must be prevented. But on the other hand, the institution of fatwa also gives room for the possibility of abortion if it is seen it will be able to bring good to the pregnant mother and her family.